2019
DOI: 10.31018/jans.v11i2.2052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vermicompost and urea on the seed germination and growth parameters of Vigna mungo L. and Vigna radiata L. Wilzek

Abstract: Growth attributes of Vigna mungo and Vigna radiata crop influenced by level and type of fertilizers. The present study was carried out to evaluate and compare the effects of organic (vermicompost) and inorganic (urea) fertilizers on the germination percentage and seedling growth of V. radiata (Green gram) and V. mungo (Black gram). Fresh weight and dry weight of tested plant samples at 10th days of growth stage were also determined. Vermicompost was used as organic fertilizer and urea as inorganic fertilizer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The favourable effect of vermicompost and RDF resulted in a significant improvement in yield attributes and an unexpected increase in seed and stover yield of blackgram. These findings agree with those of Bakthavathsalam and Deivanayaki [11], Geetha and Velayutham [12], Bhattacharya et al [13], and Hussain et al [14]. Shashi Kumar et al [15].…”
Section: Effect Of Integrated Nutrient Management On Yield Attributes...supporting
confidence: 92%
“…The favourable effect of vermicompost and RDF resulted in a significant improvement in yield attributes and an unexpected increase in seed and stover yield of blackgram. These findings agree with those of Bakthavathsalam and Deivanayaki [11], Geetha and Velayutham [12], Bhattacharya et al [13], and Hussain et al [14]. Shashi Kumar et al [15].…”
Section: Effect Of Integrated Nutrient Management On Yield Attributes...supporting
confidence: 92%
“…While, the lowest stem dry weight plant -1 (1.19 g) was found in no application of manures and fertilizer. Likewise, Bhattacharya et al (2019) and Zannat et al (2020) also found parallel result in respect of dry weight which confirms the present findings. Root dry weight plant -1 (g) differed insignificantly with organic and inorganic fertilizer doses at 40 and 50 DAS (Figure 1F).…”
Section: Growth Characters Of Black Gram As Influenced By Combined Ap...supporting
confidence: 91%
“…weight of black gram as well as a significant improvement in yield parameters (Bhattacharya et al, 2019).…”
Section: Yield and Yield Contributing Characters Of Black Gram As Inf...mentioning
confidence: 99%
See 1 more Smart Citation